PENGARUH VARIASI LATIHAN PASSING BAWAH DENGAN MODEL HURUF TERHADAP HASIL PASSING BAWAH BOLA VOLI PUTRI KLUB TVRI MEDAN TAHUN 2021 - Rezma Annisa Fitri; Yan Indra Siregar (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
This study aims to determine whether the variation of under passing with the letter model can improve the results of under-passing in the Medan TVRI club volleyball athletes in 2020, the exercise of the under-passing variation with the letter model is an exercise that can help improve the under-passing technique in the game.. test after the end of the workout in the last week. Hypothesis analysis, namely, the effect of the variation of the under-passing training with the letter model on the under-passing of volleyball athletes of the Medan TVri club female athletes in 2021, obtained a Thitung hypothesis test of 3,35 Furthermore, compared with the t table with dk = n-1 = 10-1 = 9 at the significant level α = 0.05 = 2.26. In the hypothesis testing criteria it is stated that at tcount> ttable (3,25> 2.26) with α = 0.05 then Ho is rejected and Ha is accepted. So it can be concluded that there is a significant effect of under-wall passing practice on under-passing with variations of volleyball letters in women's volleyball athletes at the Medan TVRI club in 2021.